Accuracy Characteristics of the Selected Diagnostics Methods and the Adjustment of Geodetic Observations - Kulupa, Martyna; Magda, Paulina; Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of the adjustment of the experimental horizontal geodetic network using the classical method and the estimation of strengths in identifying observations with gross error and analyzing the accuracy of the obtained results. The presented analyses were made considering the possibility of their use in implementation networks and measurement and control networks used for monitoring building structures.
Keywords: geodetic observations; gross errors; robust estimation; horizontal network; accuracy analysis; obserwacje geodezyjne; błędy; estymacja; osnowa pozioma; analiza dokładności